2018
DOI: 10.1177/0961203318804922
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of allogeneic mesenchymal stromal cells transplantation for lupus nephritis

Abstract: Animal and human studies have suggested the potential of mesenchymal stromal cells (MSCs) to treat systemic lupus erythematosus (SLE). Here, we present the results of compassionate MSC treatments for three SLE patients to provide the proof of concept for a randomized and controlled clinical trial. Three patients of different ethnicities who suffer from chronic SLE, and who presented with class IV active proliferative nephritis confirmed by biopsy, were treated with allogeneic MSCs from healthy donors. Ninety m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 15 publications
3
44
0
1
Order By: Relevance
“…Notably, the SLE and rheumatoid arthritis pathways were also among the pathways identified as having the largest significant difference by KEGG analysis. These results are consistent with those of a previous study and emphasize the importance of MSC-mediated immunoregulation of monocytes in the pathogenesis and clinical treatment of autoimmune diseases [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the SLE and rheumatoid arthritis pathways were also among the pathways identified as having the largest significant difference by KEGG analysis. These results are consistent with those of a previous study and emphasize the importance of MSC-mediated immunoregulation of monocytes in the pathogenesis and clinical treatment of autoimmune diseases [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…On these bases, recent data suggest that, independent of the source, MSCs from SSc patients may be pre-committed in their differentiative behaviour toward myofibroblast, conditioned by both the cytokines and the metabolic milieu, specific of the disease 3,18,22,23 . These data partially mirror what showed in another autoimmune disease, the Systemic Lupus Erythematosus (SLE) 24 , and lead to speculate that in the field of regenerative medicine, an allogeneic rather than an autologous MSC-based therapy might be preferable for future treatments. Furthermore, it has been shown that allogenic MSCs infusion is a safe therapy for patients with autoimmune disease, including SSc patients 25 .…”
Section: Introductionsupporting
confidence: 55%
“…Two patients had early, durable, and substantial complete remissions, while the third patient achieved a partial remission, which permitted reduction of medication doses by 50-90%. Proteinuria levels were improved dramatically during the first month after treatment, and the ameliorations were sustained throughout the 9-month follow-up period [173]. In contrast, a recently published multicenter, randomized, double-blind, placebo-controlled clinical trial in 18 patients with World Health Organization class III or IV LN failed to show any beneficial effect of hUC-MSCs [174].…”
Section: Mesenchymal Stem/stromal Cellsmentioning
confidence: 90%